De Stichting Godecharle, 1871-1971. (Brussel : Provinciale Commissie voor Studiebeurzenstichtingen van Brabant, 1971)
Baele, Johan ; Baisieux, Albert ; Barmarin, Elisabeth ; Bastien, Alfred ; berger, Pol ; Bonduelle, Paul ; Bourgonjon, Clara ; Braem, Renaat ; De Braey, Michel ; Brande, Frans Van Den ; De Brichy, Charles ; Broerman, Eugène ; Camus, Gustave ; Cluysenaar, John ; Colfs, Peter ; Collard, Charles ; Coolens, Bert (Berten, Robert) ; Courtens, Alfred ; Courtens, Antoine ; D'Haveloose, Marnix ; Debonnaires, Fernand ; Deckers, Edward ; Demey, Emile ; Desmare, Jacqueline ; Dierickx, José ; Dierickx, Karel ; Dubois, Paul ; English, Joe ; Van Esbroeck, Eduard ; Van Esbroeck, Pol ; Eyckermans, Lode ; François, Solange ; Ghysels, Jean-Pierre ; Hendrickx, Jean ; Horta, Victor ; Hupet, André ; Kockerols, Adolphe ; Lambeau, Georges ; Lambot, Emile ; Leroy, Christian ; Leveque, Auguste ; Van Lierde, Nadine ; Loo, Jan Vander ; Lussie, Jacques ; Maeremans, Viktor ; Marin, Jacques ; De Meuse, Eliane ; Navez, Léon ; Van Neck, Joseph ; Nocquet, Paul ; Opsomer, Isidoor ; Peire, Luc ; Poot, Rik ; Pycke, François ; Reusens, Geert ; Rombaux, Egide ; Rousseau, Victor ; Van Saene, Maurits ; Saintenois, Jean-Pierre ; Schelck, Maurice ; Smet, Arthur ; Spilliaert, Pol ; Van Strydonck, Guillaume ; Swyncop, Philippe ; Teller, Christine ; Vandebroek, Pol ; Wallet, Gustave ; Wante, Ernest ; Wilfart, Jean
boek